Early childhood education focused on the inclusion of ASD students - Souza Correa Costa, Fernanda Aparecida de [UNESP]; Zanata, Eliana Marques [UNESP]; Messias Fialho Capellini, Vera Lucia [UNESP] (Editora Univ Leopoldlanum, 2018)
School inclusion, proposal in which all students are accepted and recognized regardless of their individual characteristics, is currently posing schools, from kindergarten on, the challenge of developing teaching practices that promote the learning of all, given that Early Childhood education has been the first educational level of elementary education since the enactment of the 1996 National Education Guidelines and Bases law. In this sense, this study is part of the results of a research project on the inclusion of students with autism spectrum disorder (ASD) in early childhood education. It aims to discuss some considerations about the historical process of school inclusion and its current context, identify early childhood education as the beginning of students' coexistence with diversity, aiming to promote the inclusion of ASD students, and present teaching concepts and implications taking these children's school inclusion into account.
Keywords: Inclusive Education; Autism Spectrum Disorder; Early Childhood Education; Inclusive Teaching Practices